DEVELOPMENT OF LEGAL REGULATION OF ELECTRONIC ACCESS SYSTEM TO EMISSIONS INTO THE ATMOSPHERE AIR - Proskura, Ganna M. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article reveals the issue of developing an electronic access system for information on emissions into the air. The international and national legislation on access to information on emissions into the air is analyzed. Methods of research: the list of normative legal acts and international dossiers in this field is determined. The methodological basis of the research comprise general scientific methods of scientific knowledge, such as integrated and interdisciplinary. Results: the main directions of further development of the updated system of accounting and control of emissions are determined, in particular, on the Internet resources. It is concluded that the formation and further implementation of a comprehensive state policy in the field of climate change, harmonized with international law, is a complex and urgent task. It is necessary to establish a clear accounting of emissions for all forms of pollutants. Discussion: problems of national and international legislation and implementation of norms of foreign legislation to the norms of domestic legislation in the field of development of the electronic system for access to information on emissions into the air.